Social responsibility in the context of universities: a bibliographic debate (Research, Society and Development, 2022)
Social responsibility is a topic that has gained increasing prominence within organizations of all areas, levels and size of its complexity. The understanding that all those who are directly or indirectly influenced by the organization's activities is no longer a competitive advantage, but a matter of necessity in modern society. The present study made use of a bibliographic analysis on the subject in general, and then proceeded to an analysis of the role of universities in this process. It was possible to perceive that universities play an extremely important role in this process, as they form and make available the best talents for the competitive market, who will make decisions for the future. However, arguments were also found that emphasize capitalist thinking in the way of shaping student values, where universities often surrender to economic desires and leave social responsibility in the background. In this way, the present study contributed to understanding the importance of universities in the process of building social responsibility, but emphasizes that, like many modern organizations, it may end up following their actions only through the bias of the economic importance of the activities.